Modern education of future teacher of physical culture in the conditions of informatization of educational space - Dragnev Y.V (Kharkov National Pedagogical University, 2012)
The informatization of the educational space is determined by the organizational, scientific-technical, educational processes, which update the creation of the unified information and educational space for the comprehensive use of information technologies in educational process of a future teacher of physical culture at the higher school. Stated that the integration and expansion of the educational space of the orients the higher school not only in the preparation of the literate student on the issues of information culture, but also to help the younger generation in the mastery of basic social abilities and skills in conditions of informatization of the educational space.